Performance of DETECT pulmonary arterial hypertension algorithm according to the hemodynamic definition of pulmonary arterial hypertension in the 2022 European Society of Cardiology and the European Respiratory Society Guidelines - Distler, Oliver; Bonderman, Diana; Coghlan, J. Gerry; Denton, Christopher P.; Grünig, Ekkehard; Khanna, Dinesh; McLaughlin, Vallerie V.; Müller-Ladner, Ulf; Pope, Janet E.; Vonk, Madelon C.; Di Scala, Lilla; Lemarie, Jean-Christophe; et al. (Arthritis & rheumatology, 2024)
Objective The evidence-based DETECT pulmonary arterial hypertension (PAH) algorithm is frequently used in patients with systemic sclerosis (SSc) to help clinicians screen for PAH by using noninvasive data to recommend patient referral to echocardiography and, if applicable, for a diagnostic right-sided heart catheterization. However, the hemodynamic definition of PAH was recently updated in the 2022 European Society of Cardiology (ESC)/European Respiratory Society (ERS) guidelines. The performance of DETECT PAH in identifying patients with a high risk of PAH according to this new definition was assessed. Methods In this post hoc analysis of DETECT, which comprised 466 patients with SSc, the performance of the DETECT PAH algorithm in identifying patients with a high risk of PAH as defined in the 2022 ESC/ERS guidelines (mean pulmonary arterial pressure [mPAP] >20 mm Hg, pulmonary capillary wedge pressure [PCWP] ≤15 mm Hg, and pulmonary vascular resistance >2 Wood units) was assessed using summary statistics and was descriptively compared to the known performance of DETECT PAH as defined in 2014, when it was developed (mPAP ≥25 mm Hg and PCWP ≤15 mm Hg). Results The sensitivity of DETECT PAH in identifying patients with a high risk of PAH according to the 2022 ESC/ERS definition was lower (88.2%) compared to the 2014 definition (95.8%). Specificity improved from 47.8% to 50.8%. Conclusion The performance of the DETECT algorithm to screen for PAH in patients with SSc is maintained when PAH is defined according to the 2022 ESC/ERS hemodynamic definition, indicating that DETECT remains applicable to screen for PAH in patients with SSc.
Erstmals veröffentlicht: 25 December 2023
Gesehen am 01.07.2024